Jane Eyre - Bronte, Charlotte; With an Introduction by Zahur Ahmad (England Puffin Books, 1994)
In early nineteenth-century England, an orphaned young woman accepts employment as a governess and soon finds herself in love with her employer who has a terrible secret. Charlotte Bronte's novel about the passionate love between Jane Eyre, a young girl alone in the world, and the rich, brilliant, domineering Rochester has enthralled every kind of reader, from the most critical and cultivated to the youngest and most unabashedly romantic, ever since its publication in 1847. It lives as one of the great triumphs of storytelling and as a moving affirmation of the prerogatives of the heart in the face of disappointment and misfortune.
With Compliments from Dr. Ammara Mazhar CMH, Multan
Keywords: Governesses -- Fathers and Daughters -- Fiction